Changes in H+-ATP Synthase Activity, Proton Electrochemical Gradient, and pH in Pea Chloroplast Can Be Connected with Variation Potential - Sukhov, Vladimir; Surova, Lyubov; Morozova, Ekaterina; Sherstneva, Oksana; Vodeneev, Vladimir (Frontiers in Plant Science, 2016)
Local stimulation induces generation and propagation of electrical signals, including the variation potential (VP) and action potential, in plants. Burning-induced VP changes the physiological state of plants; specifically, it inactivates photosynthesis. However, the mechanisms that decrease photosynthesis are poorly understood. We investigated these mechanisms by measuring VP-connected systemic changes in CO2 assimilation, parameters of light reactions of photosynthesis, electrochromic pigment absorbance shifts, and light scattering. We reveal that inactivation of photosynthesis in the pea, including inactivation of dark and light reactions, was connected with the VP. Inactivation of dark reactions decreased the rate constant of the fast relaxation of the electrochromic pigment absorbance shift, which reflected a decrease in the H+-ATP synthase activity. This decrease likely contributed to the acidification of the chloroplast lumen, which developed after VP induction. However, VP-connected decrease of the proton motive force across the thylakoid membrane, possibly, reflected a decreased pH in the stroma. This decrease may be another mechanism of chloroplast lumen acidification. Overall, stroma acidification can decrease electron flow through photosystem I, and lumen acidification induces growth of fluorescence non-photochemical quenching and decreases electron flow through photosystem II, i.e., pH decreases in the stroma and lumen, possibly, contribute to the VP-induced inactivation of light reactions of photosynthesis.